Gender, the Welfare State, and Public Employment: A Comparative Study of Seven Industrialized Countries - Janet C. Gornick; Jerry A. Jacobs (Luxembourg Income Study (LIS), 1997)
This paper explores the influence of government employment on the gender gap in earnings in seven countries, using data from the Luxembourg Income Study (LIS). The size of the public sector and women's concentration in government employment varies widely across industrialized countries. We develop and test predictions about how the public/private earnings differential varies across countries. The results indicate marked variation across liberal, conservative, and social democratic welfare states, but reveal a number of uniformities as well. We find that public-sector workers earn more, on average, than those working in the private sector in most countries in our sample. The smallest public-sector earnings premia are found in the social democratic countries and the largest are evident in the liberal welfare states. Thus, public employment provides relatively few but comparatively high-paying jobs for women in liberal welfare state, while the social democracies government positions are more numerous but comparatively low-paying. We discuss the implications of these results for theory and research on gender and the welfare state.
Keywords: 330; Weibliche Arbeitskräfte; Vergütungssystem im öffentlichen Dienst; Vergleich; Geschlecht; Industrieländer